Penerapan Pembelajaran Edutainment Model If History dalam Program Penugasan Dosen (PDS) Di SMAN 8 Bandung - Wawan Darmawan; Teni Kurniawati; Desi Rusmiati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
This paper resulted from authors’ activities after lectured in PDS (Penugasan Dosen di Sekolah /Lecturer Assignment in Schools) which programmed by the Directorate General of Learning and Student Affairs, the Ministry of Research, Technology, and Higher Education. During the PDS program, the authors have implemented edutainment learning in Class XI of SMAN 8 Bandung which is expected to provide a pleasant atmosphere in historical learning. Edutainment learning mainly focused on the ability of students to become historical figure (if history). Provision of subject material in class supported by the action research model that divides into four stages, namely planning, implementing, observing, and reflecting so that it can be used as further corrective actions. The data collection techniques using observation, interviews, and study documentation. Based on findings it can be explained that the edutainment learning of if history’s model has brought students present in the studied event’s atmosphere by “present” as actors in history. Participants seemed enthusiastic to follow the learning process which relaxed, fun, and free from tension in each stage of learning, starting from the initial to the final meeting. If history model becomes easier for students to catch with when an event is delivered with monologue teaching styles combination. In this case, students understand easier regarding the role play and discovered historical facts with their own language so that history is no longer impressed as memorizing facts.